Characterization of Plasma Extrachromosomal Circular DNA in Gouty Arthritis - Pang, Jingyuan; Pan, Xiaoguang; Lin, Ling; Li, Lei; Yuan, Shuai; Han, Peng; Ji, Xiaopeng; Li, Hailong; Wang, Can; Chu, Zhaobin; Wu, Haoru; Fan, Guangyi; et al. (Frontiers in Genetics, 2022)
Objective: Extrachromosomal circular DNA elements (eccDNAs) are known for their broad existence in cells and plasma, which may potentially play important roles in many biological processes. Our aim was to identify potentially functional or marked eccDNAs in gout patients. Methods: The Circle-Seq approach was applied for eccDNA detection from plasma in acute gout patients and healthy controls. Further analysis was performed on the distribution of genomic elements and eccDNA gene annotations in two groups. Results: We detected 57,216 and 109,683 eccDNAs from the acute gout and healthy control plasma, respectively. EccDNAs were mapped to the reference genome to identify diverse classes of genomic elements and there was no significant difference of eccDNAs on genomic element annotation between gout and control group. A total of 256 eccDNA-associated genes were detected as gout unique eccDNA genes, including COL1A1 and EPB42, which potentially contribute to hyperuricemia and gout, and a couple of genes involved in inflammation or immune response. Enrichment analysis showed that these eccDNA genes were highly correlated with defense response, stress response, and immune and inflammatory responses, including T cell receptor signaling pathway, Fc epsilon RI signaling pathway, and JAK-STAT signaling pathway. Conclusion: Our discovery reveals the novel potential biological roles of plasma eccDNAs in gouty arthritis.